2014
DOI: 10.3923/aje.2015.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor Factors of Early Initiation of Breastfeeding among Mothers in Rural District Bone, South Sulawesi, Indonesia

Abstract: Early initial breastfeeding is a new method of breastfeeding by letting babies find their mother's breast by themselves soon after delivery. Early initial breastfeeding at the first hour is believed to increase the success of exclusive breastfeeding. But the practice of this method in Indonesia is still low, even after having support by policy. This research is trying to find out the potential factor obstructed the implementation of early initial breastfeeding. Cross sectional study was done in local governmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This study also found that women from Sumatra and Sulawesi had lower EIB rates in 2017 compared to other regions. Some local studies indicate that limited knowledge of EIB for both health workers and mothers, and the lack of local government guidelines to support EIB, cause suboptimal implementation of EIB in both regions [53,54].…”
Section: Previous Studiesmentioning
confidence: 99%
“…This study also found that women from Sumatra and Sulawesi had lower EIB rates in 2017 compared to other regions. Some local studies indicate that limited knowledge of EIB for both health workers and mothers, and the lack of local government guidelines to support EIB, cause suboptimal implementation of EIB in both regions [53,54].…”
Section: Previous Studiesmentioning
confidence: 99%
“…Another reason for the delayed initiation of breastfeeding in the current study was a lack of knowledge of how to initiate breastfeeding. Lack of breastfeeding counseling and midwife support has been previously identified as a cause for increased delay in the initiation of breastfeeding ( 39 , 40 ). These authors emphasize the importance of breastfeeding education during antenatal visits and support by midwives and birth attendants post-delivery to ensure early breastfeeding initiation.…”
Section: Discussionmentioning
confidence: 99%
“…18 The provision of midwife support to pregnant women was found to increase the success of EIB implementation by 17.5 times. 19 The first hour after birth is crucial for midwives to perform EIB. The implementation of EIB is successful if it is carried out as soon as possible after delivery, and the process lasts for 60 minutes or more.…”
Section: Introductionmentioning
confidence: 99%